The Relationship Between Educational Videos on Proper Pushing and Breathing Techniques and the Knowledge of Women of Reproductive Age in Kebun Dua Ratus, Kalideres District, Jakarta Barat - Sumarti Sumarti; Hastin Catur Wulansari (Universitas Teuku Umar, 2025)
Knowledge of proper pushing and breathing techniques is important for women of childbearing age (WCA) to prepare for a safe and comfortable delivery. Educational videos are considered an effective medium for increasing knowledge. This study aimed to determine the relationship between the provision of educational videos on proper pushing and breathing techniques and the knowledge of women of childbearing age in Kebun Dua Ratus, Kalideres District, West Jakarta. This study employed a cross-sectional design. The sample consisted of 30 women of childbearing age selected using purposive sampling. Data were collected using a questionnaire, and the study was conducted in RT 03 Kebun Dua Ratus. The analysis showed a p-value of 0.001, indicating a statistically significant relationship between the provision of educational videos and increased knowledge of proper pushing and breathing techniques among women of childbearing age. Women who received educational videos demonstrated better knowledge of proper pushing and breathing techniques compared to those who did not receive educational videos.